Follow-up of vestibular function in bilateral vestibulopathy. Issue 3 (17th July 2007) - Zingler, V C; Weintz, E; Jahn, K; Mike, A; Huppert, D; Rettinger, N; Brandt, T; Strupp, M
Abstract : Objective: Bilateral vestibulopathy (BV) leads to a bilateral deficit of the vestibulo-ocular reflex and has various aetiologies. The main goal of this study was to determine the frequency and degree of recovery or worsening of vestibular function over time. Methods: 82 patients (59 males, 23 females; mean age at the time of diagnosis 56.3 (SD 17.6) years) were re-examined 51 (36) months after the first examination. All patients underwent a standardised neuro-ophthalmological and neuro-otological examination. Electronystagmography with bithermal caloric irrigation was analysed by measurement of the mean peak slow phase velocity (SPV) of the induced nystagmus. Patients evaluated the course of their disease in terms of balance, gait unsteadiness and health related quality of life. Results: Statistical analysis of the mean peak SPV of caloric induced nystagmus revealed a non-significant worsening over time (initial mean peak SPV 3.0 (3.5)°/s vs 2.1 (2.8)°/s). With respect to subgroups of aetiology, only patients with BV due to meningitis exhibited an increasing, but non-significant SPV (1.0 (1.4)°/s vs 1.9 (1.6)°/s). Vestibular outcome was independent of age, gender, time course of manifestation and severity of BV. Single analysis of all patients showed that a substantial improvement ⩾5°/s occurred in two patients on both sides (idiopathic n = 1, Sjögren's syndrome n = 1) and in eight patients on one side (idiopathic n = 6, meningitis n = 1, Menière's disease n = 1). In 84% of patients there was impairment of their health related quality of life (42% slight, 24% moderate, 18% severe). Forty-three per cent of patients rated the course of their disease as stable, 28% as worsened and 29% as improved. Conclusions: Our data support the view that more than 80% of patients with BV do not improve. Thus the prognosis of BV is less favourable than assumed.